Nanoclay - Recent Advances, New Perspectives and Applications 2022
DOI: 10.5772/intechopen.105903
|View full text |Cite
|
Sign up to set email alerts
|

Organoclay Nano-Adsorbent: Preparation, Characterization and Applications

Abstract: Organoclay has a tremendous impact on both fundamental studies and practical applications in numerous fields. In this context, this chapter investigates the performance of Organoclay in wastewater treatment. In particular, the adsorption of various hazardous substances has been reviewed. This study aims to give an overview of the preparation methods of Organoclay. The second purpose was to discuss the removal efficiency and reliability of various pollutants by organoclay. The third goal discussed the isotherms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
1
0
Order By: Relevance
“…Psidium guajava leaves extract was utilized to synthesize green nickel oxide nanoparticles (PG-NiONPs) [10]. Yahya et al [53] investigated the characterization, preparation and application of organoclay nano-adsorbent for the removal of pollutants from wastewater. They concluded that the Organoclay could be considered a cheap and efficient adsorbent for the removal of most of the chemical pollutants from wastewater that could be of socioeconomic and environmental relevance.…”
Section: Nanotechnology For Sorption Processesmentioning
confidence: 99%
“…Psidium guajava leaves extract was utilized to synthesize green nickel oxide nanoparticles (PG-NiONPs) [10]. Yahya et al [53] investigated the characterization, preparation and application of organoclay nano-adsorbent for the removal of pollutants from wastewater. They concluded that the Organoclay could be considered a cheap and efficient adsorbent for the removal of most of the chemical pollutants from wastewater that could be of socioeconomic and environmental relevance.…”
Section: Nanotechnology For Sorption Processesmentioning
confidence: 99%
“…The most common surfactants used to prepare organoclay are cationic (especially quaternary ammonium salts), zwitterionic and nonionic. When using cationic and zwitterionic surfactants, clays are modified through the exchange of exchangeable cations present in the interlayer space, whereas in the case of nonionics, modification can occur via dipole-ion interactions, thus leading to hybrid materials with dual behavior, hydrophilic-hydrophobic [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%